Left Atrial Appendage Closure Under Intracardiac Echocardiographic Guidance: Feasibility and Comparison With Transesophageal Echocardiography. Issue 10 (28th September 2016) - Matsuo, Yae; Neuzil, Petr; Petru, Jan; Chovanec, Milan; Janotka, Marek; Choudry, Subbarao; Skoda, Jan; Sediva, Lucie; Kurabayashi, Masahiko; Reddy, Vivek Y.
Abstract : Background: Transcatheter left atrial appendage closure is an alternative therapy for stroke prevention in atrial fibrillation patients. These procedures are currently guided with transesophageal echocardiography and fluoroscopy in most centers. As intracardiac echocardiography (ICE) is commonly used in other catheter‐based procedures, we sought to determine the safety and effectiveness of intracardiac echocardiography–guided left atrial appendage closure with the Watchman device. Methods and Results: A total of 27 patients (11 males, 77.0±8.5 years) with atrial fibrillation receiving Watchman left atrial appendage closure under intracardiac echocardiography guidance at a single center were investigated. All patients were implanted successfully. There were no major procedural complications. The overall procedure‐related complication rate was 14.8%, mainly due to access site hematoma. Transesophageal echocardiography demonstrated successful closure of the left atrial appendage in all patients at 45 days after device implant. Conclusions: Transcatheter left atrial appendage closure with intracardiac echocardiography guidance is safe and feasible.